Arginine-specific gingipains (RgpA/RgpB) knockdown modulates neutrophil machinery - Tubero Euzebio Alves, Vanessa (2024)
Background: Gingipains are important virulence factors present in Porphyromonas gingivalis. Arginine-specific gingipains (RgpA and RgpB) are critically associated with increased proteolytic activity and immune system dysfunction, including neutrophilic activity. In this study, we assessed the impact of gingipains (RgpA and RgpB) on neutrophil function. Methods: Peripheral blood samples were obtained; neutrophils were isolated and incubated with P. gingivalis A7436, W50, and the double RgpA/RgpB double knockout mutant E8 at MOI 20 for 2 hours. Neutrophil viability was assessed by Sytox staining. Phagocytic capacity and apoptosis were measured by flow cytometry. Superoxide release was measured by superoxide dismutase and cytochrome c reduction assay. Gene expression of TLR2, p47-phox, p67-phox, and P2 × 7was measured by qPCR. Inflammatory cytokine and chemokine production was measured by IL-1β, IL-8, RANTES, and TNF-α in cell supernatants. Results: Neutrophil TLR2 gene expression was reduced in the absence of RgpA/RgpB (p < 0.05), while superoxide production was not significantly impacted. RgpA/RgpB−/− significantly impaired neutrophil phagocytic function (p < 0.05) and increased TNF-α production when compared with the wild-type control (p < 0.05). Neutrophil apoptosis was not altered when exposed to RgpA/RgpB−/− E8 (p > 0.05). Conclusion: These data suggest that arginine-specific gingipains (RgpA/RgpB) can modulate neutrophil responses against P. gingivalis infection.